(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study investigates user perception, affordability concerns, and willingness to pay (WTP) for the Trans Sumatera Toll Road in Riau Province, a newly tolled region where road pricing is still unfamiliar to many residents. Using 412 survey responses analyzed through descriptive statistics, cross-tabulations, and regression models, the study reveals a consistent gap between perceived effectiveness and perceived affordability. While 74 percent of users view the toll road as effective in improving travel speed and comfort, only 41 percent consider the tariff fair. Comparative affordability analysis shows that toll rates in Sumatera account for a higher share of income than those in Java and several benchmark countries, reinforcing local concerns about cost burden. WTP results indicate that users are willing to pay higher tariffs for occasional travel but become significantly more price-sensitive for frequent use, as confirmed by the Wilcoxon signed-rank test. Regression findings show that income, trip purpose, and usage frequency influence WTP, whereas information clarity is the strongest and most consistent predictor of both positive perception and greater payment willingness. These findings highlight the importance of communication transparency and locally adaptive pricing strategies for promoting public acceptance and ensuring equitable toll road use in emerging regions.